2011
DOI: 10.1200/jco.2011.34.9068
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging–Detected Tumor Response for Locally Advanced Rectal Cancer Predicts Survival Outcomes: MERCURY Experience

Abstract: MRI assessment of TRG and CRM are imaging markers that predict survival outcomes for good and poor responders and provide an opportunity for the multidisciplinary team to offer additional treatment options before planning definitive surgery. Postoperative histopathology assessment of ypT and CRM but not post-treatment N status were important postsurgical predictors of outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
402
6
19

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 598 publications
(437 citation statements)
references
References 24 publications
10
402
6
19
Order By: Relevance
“…A NAC phase III trial also provides excellent opportunities for linked translational research aimed at identifying biomarkers predictive of longterm outcome. Such biomarkers could be derived from imaging such as tumour regression grade (TRG) or response of EMVI [53,54]. Alternatively they could be pathological, such as changes in TRG or in tumour cell density (TCD) [55,56], or molecular, such as stratifiers of response to chemotherapy and radiotherapy.…”
Section: Addition Of Nac To Preoperative Treatmentmentioning
confidence: 99%
“…A NAC phase III trial also provides excellent opportunities for linked translational research aimed at identifying biomarkers predictive of longterm outcome. Such biomarkers could be derived from imaging such as tumour regression grade (TRG) or response of EMVI [53,54]. Alternatively they could be pathological, such as changes in TRG or in tumour cell density (TCD) [55,56], or molecular, such as stratifiers of response to chemotherapy and radiotherapy.…”
Section: Addition Of Nac To Preoperative Treatmentmentioning
confidence: 99%
“…These include post-treatment T staging (ymrT), volume reduction between baseline and posttreatment, [15] and modified Response Evaluation Criteria in Solid Tumors (RECIST) measurement [16]. In addition to these assessment criteria, the MERCURY study group has developed an MRI-based tumor regression grading (ymrTRG) system by applying the principles of histopathology ypTRG [17,18] and showed that MRI assessment of ypTRG following preoperative therapy predicted survival [17]. It has been suggested that there may 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 be benefits in prolonging the interval between end of NACRT and surgery beyond the common 6-8 weeks [19][20][21], but evidence is limited.…”
Section: Introductionmentioning
confidence: 99%
“…According to data from the MERCURY study [111], rectal cancer is one of the best oncological settings to test the relevance of dynamic techniques aspotential predictive indicatorsof neoadjuvant treatment efficacy in LARC. Therefore, future translational studies should be also aimed to incorporate imaging studies in patients treated with new targeted anticancer agents.…”
Section: Resultsmentioning
confidence: 99%